In Situ Monitoring of Nanoparticle Formation: Antisolvent Precipitation of Azole Anti-fungal Drugs. - Tajber, Lidia; McComiskey, Kate P.M.; Mugheirbi, Naila A.; Stapleton, Jack (My University, 2018)
In this work we report the effect of stabilizer choice and concentration on nanoparticle (NP) stability over time. Three different BCS class II active pharmaceutical ingredient (APIs): itraconazole (ITR), ketoconazole (KETO) and posaconazole (POS) were chosen due to their poor aqueous solubility and closely related chemical structures. Polyethylene glycol, polyethylene glycol methyl ether and polyethylene glycol dimethyl ether (DMPEG) with a molecular weight of 2000 Da were included as stabilisers. NPs were formed in situ using an anti-solvent addition, bottom up method at 25 °C. Colloidal stability was monitored using dynamic light scattering (DLS), accompanied by morphological examination of the NPs using scanning electron microscopy. Kinetic modelling indicates nanoparticle growth is driven by Ostwald ripening (OR). The presence of DMPEG causes OR growth to become an interface controlled process following a parabola trend. DMPEG encourages OR for POS NPs whilst driving the crystallisation process. The rate of OR appears to be inherent of the crystallisation pathway by which these APIs proceed. Crystallisation mechanisms are API, stabilizer type and concentration dependent. DLS is suitable as an initial systematic screening method for stabilizer selection, aiding the pharmaceutical scientist in the optimisation of nano-formulations.
PUBLISHED
Keywords: Itraconazole; Posaconazole; Ketoconazole; Ostwald ripening; Dynamic light scattering; Nanoparticle; Crystallization; Immunology, Inflammation & Infection; Nanoscience & Materials